An Analysis of Catastrophic Out-of-Pocket Health Expenditures in Ghana - Sataru, Fuseini; Twumasi-Ankrah, Kwame; Seddoh, Anthony (Frontiers in Health Services, 2022)
Introduction: Ghana implemented a universal health coverage scheme aimed at attaining financial risk protection against catastrophic out-of-pocket health expenditures. The effort has yielded mixed benefits for the different socio-economic profiles of the population. The present study estimates the incidence of catastrophic payments among Ghanaian households. Methods: The study analysed the round 7 dataset of the Ghana living Standards Survey collected between 2016 and 2017. We estimated the incidence and intensity of catastrophic payments for total household consumption and non-food consumption for a range of thresholds. The analysis further weighted the measures of catastrophic payments to determine the distribution-sensitivity. Results: As the threshold increased from 10% to 25% of total household consumption, the incidence of catastrophic payments dropped from 1.0 to 0.1%. At the 40% threshold of non-food consumption, the estimated incidence was 0.2%. For both total household consumption and non-food consumption, the concentration indices were negative at all the thresholds. The results were indicative of a higher concentration of financial catastrophe among the poorest households and significant inequalities in the incidence between the poorest and richest households. Conclusion: The study confirmed the declining trend in the general incidence of catastrophic health expenditures in Ghana. However, the incidence and risk of financial catastrophe remained disproportionately higher among the poorest households, instructive of gaps in financial risk protection coverage. The Ghana National Health Insurance Scheme must therefore strengthen its targeting and enrolment of this sub-population group to reduce their vulnerability to catastrophic payments.